Analysis of Homestay Guidelines and Stakeholder Engagement as Community Based Tourism - Marta Muslin; Dita Oki Berliyanti; Maria Ariesta Utha (International Journal Labs, 2023)
Labuan Bajo is one of the destinations chosen as a super priority destination located in the province of East Nusa Tenggara. The data obtained from the results of the study were 42% of guests stayed at homestays for 1-2 nights and 39% never had a guest. The study used a qualitative approach to analyze the guidelines for cottage management according to local culture. Homestay owners, regulators, and other stakeholders do not yet have awareness of the need to develop guidelines for homestay management practices. The tourism sector can open access to employment for all and improve the local economy so that it can contribute to the creation of sustainable development goals (SDGs 8). All these aspects can be achieved if all stakeholders work together because with partnerships, common goals will be achieved more optimally.